The Implementation of Total Quality Management (TQM) from Qur’anic Perspective and Its Problems in Schools - Aris Sutikno; Dakir Dakir; Jasiah Jasiah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to explore the implementation of Total Quality Management (TQM) from the Quranic perspective in the context of schools and madrasahs. The method used is a systematic literature review with content analysis of the Quran, tafsir, and literature related to Islamic education management. The research results show three TQM principles aligned with Quranic values: continuous improvement (islah) based on QS. Ar-Ra'd: 11, total involvement (syura) in QS. Al-Shura: 38, and customer focus as a form of service in QS. Al-Baqarah: 195. TQM implementation includes top management commitment, quality team formation, human resource training, performance measurement, and continuous evaluation. Major challenges include resistance to change, resource limitations, lack of stakeholder support, and organizational culture misalignment. Recommended solutions include intensive socialization, quality culture development, resource optimization, and using Quranic values as implementation foundation. The study concludes that integrating TQM with Quranic principles has potential to improve educational quality while strengthening student character formation. Research contributions include developing educational management models that integrate spiritual values with contemporary management principles for Islamic educational institutions